Kajian Sistem Drainase di Daerah Jalan Pemuda Kota Bogor - Titon Sadewo; Sutoyo Sutoyo (Jurnal Teknik Sipil dan Lingkungan, 2018)
Flood was a problem that often occurs in the big cities of Indonesia. High rainfall, increasing population and unappropriate urban drainage system were the factors that cause the flood problems. The purpose of the research were to identify the condition of the existing drainage channels and to analyze the amount of runoff and comparing the run off to drainage channels in Pemuda Street. The analysis was carried out with simulations using EPA SWMM 5.1. Based on field observations, the drainage system in Pemuda Street was quite good with a rectangular cross section and were constructed using concrete. Based on the simulation results, the peak discharge runoff were around 0.017 - 2.119 m3/s, and water flow in channels C5, C40, and C49 almost meet the channel capacity with a discharge of 1.49 m3/s, 0.46 m3/s, and 0.23 m3/s respectively and would be potential to become flood. To reduce the flooding potential at Pemuda Street, dimension changes were needed on C5 and C49 channels with the final dimensions of 1.02 m x 0.77 m and 0.5 m x 0.59 m. But, because of the C5 dimension was changed, so waterflow in C40 were appropriate with channel capacity and would not need dimension change.Key words: drainage, EPA SWMM 5.1, rainfall, runoff